Complexation of lysozyme with sodium caseinate and micellar casein in aqueous buffered solutions. (January 2017) - Antonov, Yurij A.; Moldenaers, Paula; Cardinaels, Ruth
Abstract: We present an extended structural and morphological study of the complexation of lysozyme (Lys) with sodium caseinate (SC) and micellar casein (MC) by means of turbidity measurements, phase analysis, dynamic, static and electrophoretic light scattering, bright-field and confocal laser scanning (CLSM) microscopy, fluorescence anisotropy and circular dichroism measurements. The solution behavior, structure, effective charge and morphology of the formed complexes as well as the protein structure within the complexes are dependent on the state of the casein molecules (SC versus MC), pH, ionic strength, and the [Cat + ]/[An − ] charge ratio (ChR). Absorption measurements indicate complexation of Lys with caseins at a pH as high as 11.29 ( I  = 0.01). At ChR>1, i.e. in excess of lysozyme, CLSM clearly showed formation of complex Lys/SC particles with a neutral core and an exterior part consisting exclusively of hydrophilic Lys macromolecules, whereas in the case of Lys/MC particles a uniform distribution of both proteins was observed. Binding of Lys with SC or MC leads to disruption of the secondary structure of Lys. Binding isotherms from fluorescence anisotropy are well described by an independent binding site model. Graphical abstract: Highlights: Structure of the complex particles is determined by the state of casein molecules. Structure of the complex particles is dependent on the charge ratio. Solubility of the complexes and their morphology are dependent on the charge ratio. Binding of Lys with caseins leads to disruption of their secondary structure.